Study of thrombotic complications in COVID-19 - B. M., Raghavendra; Khan, Imran (International Journal of Advances in Medicine, 2022)
Background: In December of 2019, severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) began to infect humans in the city of Wuhan and has rapidly become pandemic. Recent clinical trials suggested that COVID-19 related thromboembolic complications are the major cause for increased incidence of morbidity and mortality. We conducted a prospective observational study to evaluate the prevalence of vascular complications due to COVID-19 and to analyse the difference in the inflammatory markers before and after the events. Methods: Prospective observational study, conducted at department of general medicine, Bangalore Medical College, Bangalore Karnataka from 3 months, 01 August 2021 to 30 October 2020. The incidence of thrombotic events was 70.7% (53/75). The incidence of arterial thromboembolic events was 48%, involving 36 patients of the overall study population. Of these 36 patients, majority of them were suffering from cerebrovascular accident (CVA) accounting for about 12 (16%) of the patients followed by 11 (14.7%) with ischemic heart disease (IHD). About 22.66% (17/75) of patients had developed venous thromboembolic events. Of which, 13 (17.3%) patients had developed deep-vein thrombosis (DVT). Results: We observed that all the inflammatory markers had significantly increased after the onset of thrombotic events. Serum ferritin, lactate dehydrogenase (LDH), interleukin-6 (IL-6) and fibrinogen were almost raised by 50% of the pre-event values. We could not calculate the sensitivity, specificity, positive predictive value and negative predictive value for each parameter as the severity of the disease was widely distributed. Majority of these thrombotic events were observed among the patients aged >60 years and those with comorbid conditions. But there no statistically significant difference observed. Conclusions: We concluded that COVID-19 causes significantly increased surge of inflammatory markers and thereby the significantly increased prevalence of arterial and venous thrombotic events.